1981
DOI: 10.1128/jcm.13.4.688-695.1981
|View full text |Cite
|
Sign up to set email alerts
|

Metal requirements of Legionella pneumophila

Abstract: Serial passage of six strains of Legionella pneumophila and one strain of Pseudomonas aeruginosa in a liquid chemically defined medium deficient in trace metals resulted in the death of five L. pneumophila strains and very limited growth in the remaining strain and the P. aeruginosa strain. Addition of either iron or magnesium restored growth to almost normal levels in ail of the strains when early-passage inocula were used. A low concentration of magnesium stimulated growth with cobalt, copper, iron, manganes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 20 publications
2
56
0
2
Order By: Relevance
“…Even though L. pneumophila preferentially utilizes amino acids for carbon and energy, in silico analysis of the L. pneumophila genome sequence revealed that this organism is auxotrophic for the seven amino acids Arg, Cys, Ile, Leu, Met, Thr and Val (Cazalet et al, 2004;Chien et al, 2004). Furthermore, it has been shown that the amino acids Arg, Cys, Ile, Leu, Met, Ser, Thr and Val are essential for growth of L. pneumophila in vitro (Pine et al, 1979;George et al, 1980;Reeves et al, 1981;Ristroph et al, 1981;Tesh and Miller, 1981;Tesh et al, 1983;Molofsky and Swanson, 2004;Wieland et al, 2005;Eylert et al, 2010). The four amino acids, Arg, Cys, Gln and Ser, are needed to support growth in vivo (Wieland et al, 2005).…”
Section: Amino Acid Requirements Of L Pneumophilamentioning
confidence: 99%
See 2 more Smart Citations
“…Even though L. pneumophila preferentially utilizes amino acids for carbon and energy, in silico analysis of the L. pneumophila genome sequence revealed that this organism is auxotrophic for the seven amino acids Arg, Cys, Ile, Leu, Met, Thr and Val (Cazalet et al, 2004;Chien et al, 2004). Furthermore, it has been shown that the amino acids Arg, Cys, Ile, Leu, Met, Ser, Thr and Val are essential for growth of L. pneumophila in vitro (Pine et al, 1979;George et al, 1980;Reeves et al, 1981;Ristroph et al, 1981;Tesh and Miller, 1981;Tesh et al, 1983;Molofsky and Swanson, 2004;Wieland et al, 2005;Eylert et al, 2010). The four amino acids, Arg, Cys, Gln and Ser, are needed to support growth in vivo (Wieland et al, 2005).…”
Section: Amino Acid Requirements Of L Pneumophilamentioning
confidence: 99%
“…Even though L. pneumophila absolutely requires amino acids to power intracellular growth, it is auxotrophic for Arg, Cys, Ile, Leu, Met, Thr and Val (Fig. 3) (Pine et al, 1979;George et al, 1980;Reeves et al, 1981;Ristroph et al, 1981;Tesh and Miller, 1981;Tesh et al, 1983;Molofsky and Swanson, 2004;Wieland et al, 2005;Eylert et al, 2010). Surprisingly, Acanthamoebae, a primary host amoeba of L. pneumophila in the aquatic environment, is auxotrophic for Arg, Ile, Leu, Met and Val (Fig.…”
Section: Synchronization Of Amino Acid Auxotrophymentioning
confidence: 99%
See 1 more Smart Citation
“…Legionella pneumophila infects humans via inhalation of contaminated aerosols (Steinert et al, 2002). Iron is a key nutrient for most bacteria in particular for many pathogens (Leong et al, 1974;Weinberg, 1978;Reeves et al, 1981;Ratledge and Dover, 2000;Schaible and Kaufmann, 2004). It is essential as a cofactor in various enzymatic reactions like respiration, oxidative stress response or DNA replication, but can also be a toxic element at elevated intracellular concentrations by catalysing the Fenton reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Iron is essential for Legionella growth [5] and the pathogen has developed strategies for the efficient uptake of ferric (Fe 3+ ) iron using siderophores such as legiobactin [6]. Ferrous iron (Fe 2+ ) is critical for L. pneumophila growth under low-oxygen conditions in host cells, and in the mammalian lung [7].…”
Section: Introductionmentioning
confidence: 99%